KEEFEKTIFAN TEKNIK SCRAMBLE DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG PADA SISWA SMAN 2 TELUK KUANTAN KELAS XI IPS - Fitrah Sari; Nana Rahayu; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Effectiveness of Scramble Technique in Learning Japanese Vocabulary on Students Grad XI IPS Senior High School 2 Teluk Kuantan This study is discusses about the effectiveness of scramble learning technique in learning Japanese vocabulary on students of Senior High School 2 Teluk Kuantan. The purpose of this study is to know the significant difference between the learning outcomes of students who use scramble learning and who do not use scramble learning. Object of this study is the students grade XI IPS Senior High School 2 Teluk Kuantan. The object of this study is consisting of 2 classes, XI IPS I and XI IPS II. This is a quasi-experiment study. The quasi-experiment design used in this study is pretest-post test design, conducted on 2 classes : experiment class and control class. The data collection technique done with doing test. Test are pretest and post test to know student's ability of Japanese in learning Japanese vocabulary before and after given treatment. The result of this pretest and post test is processed by using statistical test with t formula manually. Based on data process, obtained value t hitung 7.95 > t tabe 1.68,which means there are significant difference between the learning outcomes of students who use the scramble learning technique and who do not use scramble learning technique in learning Japanese vocabulary on the students grad XI IPS of Senior High School 2 Teluk Kuantan.Key words : Vocabulary Learning, Scramble Learning Technique, Students grad XI IPS of Senior High School 2 Teluk Kuantan.